Matching coefficients for αs and mb to [omicron] (α s 2 ) in the MSSM - Bauer, Andreas; Mihaila, Luminita; Salomon, Jens Eric (Journal of high energy physics, 2009)
We compute the exact two-loop matching coefficients for the strong coupling constant α s and the bottom-quark mass m b within the Minimal Supersymmetric Standard Model (MSSM), taking into account ##IMG## [http://ej.iop.org/icons/Entities/calO.gif] Script O (α s 2 ) contributions from Supersymmetric Quantum Chromodynamics (SQCD). We find that the explicit mass pattern of the supersymmetric particles has a significant impact on the predictions of α s and m b at high energies. Further on, the three-loop corrections exceed the uncertainty due to the current experimental accuracy. In case of the the running bottom-quark mass, they can reach in the large tan β regime up to 30% of the tree-level value.